Genomic Comparisons of Salmonella enterica Serovar Dublin, Agona, and Typhimurium Strains Recently Isolated from Milk Filters and Bovine Samples from Ireland, Using a Salmonella Microarray - Reen, F. J. (American Society for Microbiology, 2005)
Salmonella-induced enterocolitis is the leading food-borne illness with a lethal outcome and causes millions of cases of gastroenteritis each year. We examined genomic variation among 12 environmental, veterinary, and clinical Salmonella enterica serovar Dublin, Agona, and Typhimurium strains isolated in Ireland between 2000 and 2003, as well as two clinical isolates from Canada and four archival isolates, which belonged to serovars Dublin and Agona. Using DNA-DNA hybridization to a microarray consisting of most of the predicted protein-encoding sequences of the S. enterica serovar Typhimurium LT2 genome, we identified a number of genomic regions that were absent in one or more serovars. The 34 genomic regions encoded proteins involved in sugar metabolism, transport, fimbrial and phage biogenesis, and transcriptional regulation, as well as inner and outer membrane-associated proteins. Two of the four prophages identified in strain LT2, prophages Gifsy-1 and Gifsy-2, were present in all six serovar Typhimurium strains examined. Prophage Fels-1 was absent from all 18 isolates examined, and Fels-2 was completely absent from the serovar Typhimurium isolates and the Salmonella Reference Collection B serovar Dublin strain Du2. All five Salmonella pathogenicity islands were present in all isolates. Plasmid pSLT was absent from all serovar Agona isolates, and only homologues of the spv genes were present in eight of the nine serovar Dublin strains. Only limited intraserovar diversity was found among the nine serovar Dublin, three serovar Agona, and six serovar Typhimurium isolates examined even though these isolates had extensive geographic, temporal, and source differences.